The time-use agency scale: Development and validation of a measure for Ghana and beyond - Sinharoy, Sheela; Cheong, Yuk Fai; Heckert, Jessica; Seymour, Greg; Johnson, Erin R.; Yount, Kathryn M. (Informa UK Limited, 2023)
Global health and development interventions often are predicated on the reallocation of women's time for the achievement of program objectives; yet research and programs have paid limited attention to women's preferences for and agency over their time use. This study aims to develop and validate an instrument to measure time-use agency. It follows a sequenced approach involving qualitative and quantitative research, with exploratory and confirmatory factor analyses and assessment of concurrent validity. The authors conducted surveys with women and men within an impact assessment of a livelihoods program being implemented across rural districts in Ghana. Results indicate a three-factor model with subscales for intrinsic time-use agency, voice related to time use, and decision making related to time use, which were each positively correlated with an item on satisfaction with time use. This time-use agency scale should be validated widely and used within global health and development programs.